Study on the interaction between particle shape and particle breakage of coral sand by discrete element method - Liu, Xuejun; Zeng, Kaifeng; Xiang, Fuyu; Wang, Chunhai; Hou, Xianming; Li, Yanjun (Frontiers in Earth Science, 2024)
A series of biaxial tests with different initial particle shapes, confining pressures, bond strengths and depositional angles were conducted on coral sand by using a 2D discrete element method (DEM) simulation. The interactions between particle shape and particle breakage were investigated, and their combined effects on the mechanical behavior of coral sand were analyzed. The test results showed that particle breakage considerably weakens the effect of particle shape and inherent anisotropy on shear strength. The difference between the internal friction angles of unbreakable and breakable agglomerates Δφ decreases with increasing aspect ratio AR, sphericity S, and depositional angle θ. There exists a unique relationship between the relative breakage BrDe and the input energy E for the same agglomerates, which is independent of axial strain and confining pressure. However, this relationship is significantly influenced by the agglomerate shape and depositional angle, and irregular and low depositional angle specimens are more easily broken. In addition, the evolution of the aspect ratio AR and sphericity S of agglomerates was controlled by particle breakage, regardless of the axial strain, confining pressure, bond strength and depositional angle, and these trends were determined by the initial particle shape.